If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -32x + 9 = 4x Reorder the terms: 9 + -32x = 4x Solving 9 + -32x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + -32x + -4x = 4x + -4x Combine like terms: -32x + -4x = -36x 9 + -36x = 4x + -4x Combine like terms: 4x + -4x = 0 9 + -36x = 0 Add '-9' to each side of the equation. 9 + -9 + -36x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -36x = 0 + -9 -36x = 0 + -9 Combine like terms: 0 + -9 = -9 -36x = -9 Divide each side by '-36'. x = 0.25 Simplifying x = 0.25
| -23/5t=-22 | | 3/1/2p=2/1/2 | | 1/6=x/3 | | -6+3/4(n) | | 8/2+4/10 | | 7x+7/3x | | -(6r-12s)-(6r+12s-4)= | | 3r+7s=41 | | 72y^2+9y-8=0 | | 2(3+1)(3)= | | 4+y+-1y=8+y+-1y | | x^3-7x^2-5x-1=0 | | 4/5+7/6+5 | | -3x/20=6 | | 5(-5)+(2-6)= | | 7x^2-x-2=0 | | 25x^18+7x^10= | | x^4+3*x^3*x+2=0 | | log(x)=.29 | | 5x+y^2= | | 2(6h-8)+10= | | x^2+8x-12= | | 7-(-8+1)= | | 3XY+6Y-5X-10=0 | | 12y+5v=2v-9 | | (-4pq^2)(7p^2q^4)= | | -7-(-5)=-27 | | x^2+5/2x+c=0 | | 7y^2-17y+6=0 | | 0.5^(x/13.1) | | 5(9+3x)= | | x^2-2.4x+c=0 |